Efficacy of sulfadoxine plus trimethoprim compared to management measures for the control of Eimeria parasitism in naturally infected and clinically asymptomatic sheep that were maintained in a feedlot - Zanetti Lopes, Welber Daniel; Carvalho, Rafael Silveira; Pereira, Valdomiro; Martinez, Antonio Campanha; Cruz, Breno Cayeiro; Teixeira, Weslen Fabricio [UNESP]; Maciel, Willian Giquelin [UNESP]; Costa, Alvimar Jose da [UNESP]; Soares, Vando Edesio; Lino Borges, Dyego Goncalves; Rodriguez, Fernando de Souza; Borges, Fernando de Almeida (Elsevier B.V., 2014)
The efficacy of sulfadoxine + trimethoprim in comparison to management measures for the control of Eimeria parasitism was studied in naturally infected sheep that were raised in a feedlot and were clinically asymptomatic for eimeriosis. Weight gain was also evaluated in these animals. The following groups were formed with 15 animals/group: TO!, control animals that received saline solution and maintenance of the same management measures that were performed before the study; T02, animals that received two intramuscular doses of sulfadoxine (20 mg/kg) + trimethoprim (4 mg/kg) with a 14-day interval; T03, sheep that received two intramuscular doses of sulfadoxine (20 mg/kg) + trimethoprim (4 mg/kg) with a 14-day interval plus management measures (wood shaving bedding was changed every Monday, and 30g of ammonium sulfate were applied to the bedding and other facilities were performed every Thursday, 10 mL/20 L of water); and T04, animals that received only the management measures described for the previous group. The highest efficacy rates (arithmetic mean) for the T02 group (sulfadoxine + trimethoprim at days 0 and 14) were 21.04% and 21.98% on the 14th and 28th days after the first treatment (DAFT), respectively. However, the treatment showed efficacy rates below 17% and was totally ineffective from the 70th DAFT to the end of the study. In both the T03 (chemical treatment+ management) and T04 (management only) groups, a significant (P <= 0.05) reduction of oocyst shedding per gram of feces was observed in the animals from the 14th DAFT in comparison to the control group; however, an efficacy rate above 90% was observed from the 28th DAFT. Animals belonging to the T02, T03 and T04 groups presented with alterations in weight gain of 0.57 kg, 4.30 kg and 4.53 kg, respectively, in comparison with the control animals (T01) throughout the 91-day study period. Thus, it is possible to conclude that the two-dose sulfadoxine + trimethoprim treatment, given with a 14-day interval, had little no effect on the oocyst shedding. Moreover, the adopted management measures were enough to cause a significant decrease in the animal parasite loads. (C) 2013 Published by Elsevier B.V.
Keywords: Coccidia; Sheep; Efficacy; Eimeriosis; OoPG; Sulfadoxine plus trimethoprim